How Micro-Cultures of Evaluation Practice Shape Evaluation Design - Nick L Smith (The Evaluation Center at Western Michigan University, 2013)
Background: Not applicable.   Purpose: To consider how employment settings influence evaluation design.   Setting: International conference on culturally responsive evaluation.   Intervention: Not applicable.   Research Design: Not applicable.   Data Collection and Analysis: Not applicable.   Findings: Not applicable. Keywords: evaluation design; culture; contextual influences